Safe Debt and Uncertainty in Emerging Markets : An Application to South Africa - Saxegaard, Magnus (IMF Working Papers; Working Paper ;, 2014)
This paper develops a methodology for estimating a safe public debt level that would allow countries to remain below a maximum sustainable debt limit, taking into account the impact of uncertainty. Our analysis implies that fiscal policy should target a debt level well below the debt ceiling to allow space to absorb shocks that are likely to hit the economy. To illustrate our findings we apply the methodology to estimate a safe debt level for South Africa. Our results suggest that South Africa's debt ceiling is around 60 percent of GDP, although uncertainty is high. Simulations suggest targeting a debt-to-GDP ratio of 40 percent of GDP would allow South Africa to remain below this debt ceiling over the medium-term with a high degree of confidence.